1983
DOI: 10.1111/j.1399-0004.1983.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Two different structural abnormalities of chromosome 13 in offspring of chromo‐somally normal parents with two fragile sites

Abstract: Two siblings were found with different structural abnormalities involving their maternally inherited chromosome 13. The proband exhibited a ring 13 and a small fragment: 46, XX, r(13) (pllq34), +f, while her clinically normal brother carried a dicentric Robertsonian translocation: 45, XY, dic(13;15) (pl 1;pl 1). Both parents had normal karyotypes in peripheral blood and skin fibroblasts. The structural abnormalities of chromosome 13 may be due to an unstable gonadal 13; 15 translocation in the mother. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The fragile site FRA12A was detected in peripheral-blood cells with a frequency of 2 of 63 metaphases in standard low-folate medium. 17 When we added methotrexate and BrdU to the standard medium, frequency was increased to 11 of 50 metaphases. The addition of FudR also induced the FRA12A site in fibroblast cells, with a frequency of 8 of 77 metaphases.…”
Section: Clinical Diagnosis and Chromosome Analysismentioning
confidence: 99%
“…The fragile site FRA12A was detected in peripheral-blood cells with a frequency of 2 of 63 metaphases in standard low-folate medium. 17 When we added methotrexate and BrdU to the standard medium, frequency was increased to 11 of 50 metaphases. The addition of FudR also induced the FRA12A site in fibroblast cells, with a frequency of 8 of 77 metaphases.…”
Section: Clinical Diagnosis and Chromosome Analysismentioning
confidence: 99%
“…Reports of Mules et al (1983) and Shabtai et al (1980) suggested that fragile sites have an increased risk of fetal wastage. Verkantraj and Verma (1987) demonstrated significant relationships between heritable fragile sites and chromosomal abnormalities in recurrent abortions.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant line in RC13-1 was RC13. A fragment was determined via FISH to be a marker derived from chromosome 13; this event was de novo in origin and was previously reported (Cooper et al, 1992;Mules et al, 1983). Patients RC13-2 and RC13-3 were ascertained before molecular cytogenetics; the predominant cell line in RC13-2 was the ring (87%), while three cells lost the ring.…”
Section: Chromosome 13 Ringsmentioning
confidence: 99%